A world history of architecture - Fazio, Michael, ....-; Fazio, Michael, ....- (London : Laurence King, 2009)
There are any number of architectural survey texts but this is the most comprehensive and pleasing of them all Perspective An excellent primer Sunday Times Takes on Banister Fletcher on his own ground and beats him hollow with a combination of lucid, well informed text and pictures... the images make browsing a pleasure... if I were teaching a survey course of architectural history, I would choose this as the course book
Architectuurgeschiedenis